Short-term thermal resilience and building energy flexibility using thermal mass and controlled natural ventilation - Yoon, Nari; Wu, Wentao (Energy and Buildings, 2024)
To achieve plus energy status, buildings should enhance resilient cooling and energy efficiency through natural ventilation and thermal mass. We explored the short-term thermal resilience and energy flexibility in buildings, using a mathematical model validated against experimental data. Our focus was on performance indicators such as thermal peak shedding (TPS) and thermal peak time shift (TPTS) for thermal resilience, and power peak shedding (PPS), power peak time shift (PPTS), and energy reduction (ER) for energy flexibility. A key and intriguing finding was the distinct roles played by external and internal thermal masses, which varied significantly in enhancing thermal resilience and energy flexibility. Internal mass substantially lowered peak temperatures, while external mass delayed their occurrence. For example, TPS increased up to 5.1 °C with 2 MJ/K of added internal mass, while only up to a 2.3 °C increase was observed with the same amount of added external mass. TPTS increased by 4 h with increased external mass, but only up to 1.5 h with the same amount of internal mass. For energy flexibility, external mass was more effective in reducing and delaying peak power demand. The PPS achieved by external mass was about 5 to 10 times higher than by internal mass. Model Predictive Control (MPC) consistently achieved lower temperatures and notable energy savings on milder days, effectively offsetting cooling demand on cooler days, particularly with higher cooling setpoints. The study offers insights into thermal mass design for different climates, relating to diverse experimental weather conditions. Ultimately, the research provides vital insights into optimizing thermal mass and window operations, underlining their unique contributions to building energy efficiency and comfort.
Keywords: Building simulation; Energy; Energy flexibility; Peak time; Plus energy; Predictive control; Thermal; Thermal mass; Thermal peaks; Time shifts; Analytical model; Building simulation; Energy efficiency; Plus energy; Predictive control